Is frictional lichenoid dermatitis a minor variant of atopic dermatitis or a photodermatosis - Kabir Sardana; Khushbu Goel; Vijay Kumar Garg; Alka Goel; Deepshikha Khanna; Chander Grover; Nita Khurana (Wolters Kluwer Medknow Publications, 2015)
Context: Frictional lichenoid dermatitis. Background: Frictional lichenoid dermatitis (FLE) is an entity that is probably under diagnosed and has been variably associated with either friction and/or atopy with a distinctive seasonal variation. Aims and Objectives : To study correlation of FLE with UV index and to assess its association with atopic dermatitis. Materials and Methods: A cross sectional analysis of children with FLE was done, over a period of 6 years in two tertiary hospitals. A detailed history and examination was done to assess the features of atopic dermatitis. The number of cases seen per month was compared with the mean monthly UV index. Two-tailed significance tests using Pearson's coefficient of correlation and T-test were used to interpret the data. (P < 0.05). Results: One hundred seventy-four patients were studied using the UKC criterion 17.2% of the patients had AD while xerosis (40.3%) was the predominant cutaneous finding. The number of patients seen in summer was more than in winter (P < 0.05) but there was no statistical difference between the cases in winter and spring. There was a significant correlation of the number of cases per month with UV index (P = 0.019). Almost 42% of patients gave a history of recurrence. Conclusions : FLE is probably not associated with atopic dermatitis and is likely to be related to the ambient UV index though a larger cohort with meticulous follow up may be needed to draw a final conclusion. Statistical Analysis Used: The Pearson's coefficient of correlation was used for comparing the cases per month with the UV index. The tests of hypothesis used included the paired T-tests. F-test of variance, Welch test, Wilcoxon rank sum test and the Kolmogorov-Smirnov Test. P < 0.05 was considered significant.